Role of amino acids and endogenous lipids in sperm capacitation of porcine spermatozoa - Satorre, María Mercedes (2025)
The role of oxidative substrates and metabolic pathways in providing energy for porcine sperm capacitation is not yet fully understood. Our aim was to study the role of amino acids and endogenous lipids as oxidative substrates in porcine sperm capacitation, comparing them to classical oxidative substrates such as glucose and pyruvate. Sperm samples were incubated in capacitation media with or without classical oxidative substrates. Amino acids were added in the presence or absence of salicylate, an oxidative deamination inhibitor, to assess their potential as oxidative substrates. To evaluate endogenous lipid consumption, L-carnitine (a fatty acid β-oxidation inducer) and etomoxir (a fatty acid β-oxidation inhibitor) were utilized. Sperm motility, viability, capacitation, and ammonia production were evaluated for each treatment. In capacitation media without oxidative substrates, spermatozoa preserved motility and viability but failed to undergo capacitation. The addition of amino acids to the medium without oxidative substrates increased ammonia production but did not support sperm capacitation and diminished sperm motility. These effects were not observed when glucose and pyruvate were present in culture medium, although ammonia production was still increased. The addition of L-carnitine to the medium without oxidative substrates significantly improved sperm capacitation, whereas etomoxir had no effect. Boar spermatozoa have deamination activity, but amino acids by themselves cannot sustain sperm capacitation. Contrarily, catabolism of endogenous lipids can partially support sperm capacitation when they are the only oxidative substrates available. This study provides new insights into the role of metabolic pathways during porcine sperm capacitation and has significant implications for the development of assisted reproductive technologies in this species.